Nutrition history in Pakistan - Turab, Ali; Tahir, Saman; Zaidi, Shujaat (International Food Policy Research Institute, 2018)
The Government of Pakistan (GoP) has begun to place increasing policy focus on nutrition and food security. Despite periods of high growth, Pakistan failed to achieve commensurate reductions in the prevalence of undernutrition, stunting among children, and child mortality. To accelerate progress in these areas, Pakistan joined the international Scaling Up Nutrition (SUN) movement, set up Sustainable Development Goals (SDGs) monitoring units, and has developed Multi-Sectoral Nutrition Strategies (MSNS) in each province. In this research note, we analyze the nutrition history in Pakistan before and after devolution.